Simply Calculating of dye adsorption in ZIF-8 based on external surface area - Ba Luan Tran; Thi Hong Nga Tran (Research Synergy Foundation, 2023)
We use two kinds of ZIF-8 crystals in the different external surface area to examine adsorption performance for three kinds of dye (Rhodamine B -RB, methyl orange -MO and methylene blue -MB). A t-plot method was used to determine external surface area for these samples. By establishing the trend lines from dye adsorption capacities versus external surface area, it was suggested that the RB and MO covered only on external surface area, while MB adsorbed both of inside the structure of ZIF-8 and on the outer surface. Moreover, the detailed adsorption of three dyes on the sorbent can be simulated by this method. As result, the RB and MO occupied 4.7 and 7.9 nm2 of the external surface for each molecule, respectively while that of MB included both inside the ZIF-8 structure, at a loading of 0.11 molecule per unit cell, and on the external surface with 2.3 nm2/molecule).